Homenagens do legislativo: uma etnografia dos processos simbólicos do estado - Pinto, Danilo César Souza (Universidade Federal de São Carlos, 2013)
This thesis approaches an ordinary practice by the State: public homages, like medals of honor, honorific titles and denomination of public areas. From an ethnographic research of three municipal Legislative Councils, the dynamics of these homages, the actors and factors involved were investigated. It was observed both the bureaucratic and "political" aspects of such homages. An important characteristic of these processes is that they are treated by the politicians themselves as an irrelevant assignment. However, the ethnographical data shows that these activities constitute the majority of projects presented by the council-men. In the interviews granted by council-men, officers and NGO´s members that "observe" the politicians, central terms to think about these practices, such as agreement and blandishment were noted. These terms seem to show a way of interpretation for the high number of homages. There is a pre-established agreement in the Councils to let the homages pass, because they are usually approved as blandishments to a potential or actual electorate. This thesis tries to show the subtleness and the details involved in such cases of public homag.
Keywords: Antropologia social; Etnografia; Política; Estado; Homenagem; Câmara Municipal; Ethnography; Politics; State; City Council; Homages; CIENCIAS HUMANAS::ANTROPOLOGIA